2006
DOI: 10.1002/14651858.cd001257.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acid supplementation for schizophrenia

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 54 publications
(17 reference statements)
1
40
0
Order By: Relevance
“…A recent trial offers preliminary proof of this concept, reporting that 12 weeks of fish oil treatment might by itself, without any antipsychotic medication, protect APS syndrome patients from becoming psychotic for at least 12 months (Amminger et al, 2010), when findings in chronic patients are inconclusive (Irving et al, 2006). This treatment was studied without a goal of an FDA indication; however, such a pathway to wide use of a new treatment is unusual.…”
Section: Promoting Needed Treatment and Prevention Researchmentioning
confidence: 99%
“…A recent trial offers preliminary proof of this concept, reporting that 12 weeks of fish oil treatment might by itself, without any antipsychotic medication, protect APS syndrome patients from becoming psychotic for at least 12 months (Amminger et al, 2010), when findings in chronic patients are inconclusive (Irving et al, 2006). This treatment was studied without a goal of an FDA indication; however, such a pathway to wide use of a new treatment is unusual.…”
Section: Promoting Needed Treatment and Prevention Researchmentioning
confidence: 99%
“…Other studies showed decreased polyunsaturated fatty acids in red blood cell membranes from patients with schizophrenia; the appropriateness of this finding was also supported by meta-analysis studies1112. In contrast, a Cochrane review13 indicated that the clinical effects polyunsaturated fatty acid administration for schizophrenia have been inconsistent. Hence, fatty acid disturbances might not be central to the etiology of schizophrenia.…”
mentioning
confidence: 93%
“…We would consider studies if they compared dietary advice with standard care (without dietary advice). We would not include studies if the dietary advice was given in combination with additional interventions such as exercise, or in conjunction with oral dietary supplements (including polyunsaturated fatty acid supplementation for schizophrenia (Irving 2006).…”
Section: Types Of Interventionsmentioning
confidence: 99%